Aircraft parking stand allocation problem with safety consideration for independent hangar maintenance service providers. (March 2018) - Qin, Yichen; Chan, Felix T.S.; Chung, S.H.; Qu, T.; Niu, B.
Highlights: An aircraft stand allocation problem in a maintenance hangar for an independent MRO service provider is addressed. The original no-fit polygons (NFP) are revised to separate aircraft by given safety margins. A mixed integer programming (MIP) based two-phase approach is proposed to solve the problem. A heuristic is proposed to provide the solution for practical use in real situations. Numerical studies analyze the values of the proposed models and heuristic. Abstract: An aircraft parking stand allocation problem for aircraft hangar maintenance in the context of an independent aircraft maintenance, repair and overhaul (MRO) service provider is studied. This problem arises from the increasing outsourcing maintenance requests initiated by clients that can cause congestion on certain days. Given a set of maintenance requests on a peak day that exceed the capacity of the maintenance hangar, the service provider has to select and first serve the particular subset of aircraft that maximizes their overall profits and then rearrange the remaining requests later. The objective of the proposed problem is to determine a subset of maintenance orders with maximal overall profits and a feasible parking plan on a peak day. In particular, there is to be no overlap between aircraft, and the risk of collision measured by the shortest distance between each pair of aircraft is to be minimized. To solve this problem, No-Fit Polygon (NFP) construction is adopted to prevent overlap between pairs of aircraft. A two-stage MIP approach is proposed, in which the first model is used to find the subset of maintenance orders with the maximal overall profits, while the second model maximizes the overall safety margins based on the revised NFPs. A heuristic algorithm is introduced in order to improve the efficiency of the branch-and-bound algorithm in the second stage problem. Testing instances are generated based on the real situation in an aircraft maintenance company, and the effectiveness of the proposed approaches are evaluated through computational experiments.